Can green sunrise industries lead the drive into recovery? the case of the wind power industry in China and India - Lewis, Joanna (UNIDO ViennaAT, 2010)
Examines how the global financial crisis has affected the wind power industries of the two major emerging economy wind power leaders, China and India. Examines the structure of the wind industry in each country, and government policy support that has shaped the evolutions of the industry over time. Surveys how the economic downturn has affected wind power development globally, and what this has meant for wind turbine manufacturing firms in the two countries. Assesses the outlook for the industry as well as providing recommendations for policy makers.